Heidegger and Joy (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
In this paper I consider the necessity of formulating the question of joy and I explore the kind of hearing and calling that disclose this question. A separatist stance to the different modes that existence unveils is challenged, and joy as a state-of-mind is viewed to emerge in the ecstatical-temporal shattering of resolute anxiety on existence's repetition.
Keywords: Anxiety; Authenticity; Conscience; Disclosedness; Emotions; Freedom; Inauthenticity; Joy; Mortality; Notness; Possibility; Projection; Psychotherapy; Resoluteness; Responsibility; States-of-Mind; Thrownness